2009
DOI: 10.1038/npp.2009.150
|View full text |Cite
|
Sign up to set email alerts
|

Increased Basal Synaptic Inhibition of Hippocampal Area CA1 Pyramidal Neurons by an Antiepileptic Drug that Enhances IH

Abstract: The hyperpolarization-activated cation current IH regulates the electrical activity of many excitable cells, but its precise function varies across cell types. The antiepileptic drug lamotrigine (LTG) recently was shown to enhance IH in hippocampal CA1 pyramidal neurons, revealing a potential anticonvulsant mechanism, as IH can dampen dendrito-somatic propagation of excitatory postsynaptic potentials in these cells. However, IH also is expressed in many hippocampal interneurons that provide synaptic inhibition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 30 publications
1
29
1
Order By: Relevance
“…Several studies suggest that downregulation of I h can be proepileptogenic (Peng et al, 2010). In a rat chemoconvulsant (pilocarpine) model of epilepsy, dendritic HCN channels of CA1 hippocampal neurons were substantially downregulated (Jung et al, 2007); interestingly, the activation curve of I h recorded from postpilocarpine CA1 pyramidal neuron dendrites was more negative than in sham animals, similar to the effect we have observed with E515K channels (Figs.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Several studies suggest that downregulation of I h can be proepileptogenic (Peng et al, 2010). In a rat chemoconvulsant (pilocarpine) model of epilepsy, dendritic HCN channels of CA1 hippocampal neurons were substantially downregulated (Jung et al, 2007); interestingly, the activation curve of I h recorded from postpilocarpine CA1 pyramidal neuron dendrites was more negative than in sham animals, similar to the effect we have observed with E515K channels (Figs.…”
Section: Discussionsupporting
confidence: 69%
“…The antiepileptic drug lamotrigine (LTG) increases I h in hippocampal CA1 pyramidal neurons by a depolarizing shift of the I h activation curve (Poolos et al, 2002) and/or increased I h conductance (Peng et al, 2010). This action of LTG leads to a depression of dendritic synaptic excitability (Poolos et al, 2002), supporting the view that the opposite action, i.e., I h downregulation, underlies amplification of EPSP summation and hyperexcitability.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…In a recent study, topiramate was shown to reduce the hyperexcitability in the basolateral amygdala by selectively inhibiting GluK1 (GluR5) kainate receptors on interneurons, enhancing GABAergic transmission in interneuron-to-pyramidal cell synapses, and directly enhancing GABA A receptor-mediated inhibitory currents [78] . In addition, Peng et al [79,80] concluded that the AEDs gabapentin and lamotrigine increase the hyperpolarization-activated cation current (I-H) in CA1 interneurons by decreasing EPSC frequency or increasing IPSC frequency, similar to I-H in pyramidal neurons and I-H enhancement-increased interneuron excitability. Thus, these drugs indirectly increase the spontaneous inhibition of pyramidal neurons.…”
Section: Drug Therapymentioning
confidence: 99%
“…Anticonvulsant drugs such as lamotrigine (Peng et al 2010;Poolos et al 2002) and gabapentin (Surges et al 2003) have been shown to enhance I h . The effect of enhancing I h on network behavior has received little attention.…”
Section: Membrane Properties Of L5 Pyramidal Neuronsmentioning
confidence: 99%